2003
DOI: 10.1152/physrev.00011.2003
|View full text |Cite
|
Sign up to set email alerts
|

Na+-K+Pump Regulation and Skeletal Muscle Contractility

Abstract: In skeletal muscle, excitation may cause loss of K+, increased extracellular K+ ([K+]o), intracellular Na+ ([Na+]i), and depolarization. Since these events interfere with excitability, the processes of excitation can be self-limiting. During work, therefore, the impending loss of excitability has to be counterbalanced by prompt restoration of Na+-K+ gradients. Since this is the major function of the Na+-K+ pumps, it is crucial that their activity and capacity are adequate. This is achieved in two ways: 1) by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
681
7
32

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(736 citation statements)
references
References 424 publications
16
681
7
32
Order By: Relevance
“…The effects of Ca 2+ observed in this study are also consistent with the observation that in normal muscle fibers, increased [Ca 2+ ] o hyperpolarizes the resting membrane potential (36) (16,45). Increased [Na + ] i is an important factor for activation of the Na + /K + pump (50,51), and Na + /K + pump stimulation improves membrane excitability and contractility in normal muscles with reduced Na + and/or K + gradients (52)(53)(54). We observed that partial inhibition of the pump with 0.5 μM ouabain exacerbated the K + effect on EDL muscle and drastically reduced the transient recovery observed at high [K + ] o .…”
Section: Elevated [K + ] O Produced Sustained Weakness Of Isolated Musupporting
confidence: 90%
“…The effects of Ca 2+ observed in this study are also consistent with the observation that in normal muscle fibers, increased [Ca 2+ ] o hyperpolarizes the resting membrane potential (36) (16,45). Increased [Na + ] i is an important factor for activation of the Na + /K + pump (50,51), and Na + /K + pump stimulation improves membrane excitability and contractility in normal muscles with reduced Na + and/or K + gradients (52)(53)(54). We observed that partial inhibition of the pump with 0.5 μM ouabain exacerbated the K + effect on EDL muscle and drastically reduced the transient recovery observed at high [K + ] o .…”
Section: Elevated [K + ] O Produced Sustained Weakness Of Isolated Musupporting
confidence: 90%
“…Salbutamol stimulates NKA in isolated skeletal muscle from rats (Clausen 2003), an effect that was not synergistic with muscle stimulation (Clausen and Flatman 1980). Terbutaline was recently shown to protect against an exercise-induced decline in NKA activity (Hostrup et al 2014b) and other β-adrenergic agonists also induced K + -lowering effects during continuous exercise in humans (Hallen et al 1996;Rolett et al 1990); this effect was reversed with β-blockers, resulting in greater elevations in K + Katz et al 1985).…”
Section: Blood Sampling and Analysesmentioning
confidence: 99%
“…Potassium clearance during exercise also occurs via uptake by other non-contracting or relatively inactive muscles, and also splanchnic K + uptake (Lindinger 1995;Sejersted and Sjøgaard 2000;Clausen 2003 (Hostrup et al 2014a;Collomp et al 2000;Grove et al 1995;Newnham et al 1993;Van Baak et al 2000), or in samples drawn only after completion of, rather than during exercise (Hostrup et al 2014a;Kalsen et al 2014;Hostrup et al 2014b;Larsson et al 1997;Grove et al 1995); and/or utilised oral salbutamol (Collomp et al 2000;Van Baak et al 2000;Hostrup et al 2014a;Goubault et al 2001 after prolonged cycling to exhaustion (Van Baak et al 2000), or at 5-10 min recovery after repeated 30 s sprints or repeated bouts of high intensity cycling, although greater reductions were evident at 1 or 2 min after some individual bouts (Hostrup et al 2014a). Similarly, after salbutamol inhalation (800 µg), there was no further change in antecubital venous [K + ] at 2-10 min after exhaustive cycling at 85% VO 2peak (Goubault et al 2001).…”
Section: Blood Sampling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Haller et al 9 encontraram concentrações reduzidas da bomba de sódio-potássio (Na + K + -AT Pase) na membrana da fibra muscular de pacientes com DM, provocando aumento da concentração extracelular do potássio. Isso reduz a excitabilidade da membrana durante o período de contração m u s c u l a r, explicando a diminuição do PAMC após esforço e ao estímulo repetitivo 9,10 . O mecanismo responsável pela redução da Na + K + -ATPase nos pacientes com DM não está totalmente elucidado, mas pode estar relacionado com um inadequado suprimento de ATP proveniente da glicólise para a bomba de Na + K + da fibra muscular 10 .…”
Section: Amplitude Do Pamc (µV)unclassified